Minimization of the maximum peak-to-peak gain: the general multiblock problem - Diaz-Bobillo, I.J.; Dahleh, M.A. (IEEE transactions on automatic control, 1993)
A comprehensive study of the general l/sub 1/-optimal multiblock problem and a new linear programming algorithm for computing suboptimal controllers are presented. By formulating the interpolation conditions in a concise and natural way, the general theory is developed in simpler terms and with a minimum number of assumptions. In addition, further insight is gained into the structure of the optimal solution, and different classes of multiblock problems are distinguished. This leads to a conceptually attractive, iterative method for finding approximate solutions.< >